Molecular characters of the ITS-rDNA region of two new species of Radopholus in Vietnam - Chau, Nguyen Ngoc; Phap, Trinh Quang; Moens, Maurice (Academia Journal of Biology, 2014)
Molecular characters of the ITS-rDNA region of two new species of Radopholus in Vietnam